Instagram and Students’ Higher Order Thinking Skill of Analyzing - Niken Dwiretno Galuh Agrikaltarini; Susanto Susanto; Ahmad Munir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to figure out how students implement their analyzing skill as seen from their activity in examining their peers’ narrative compositions posted in instagram. The researcher collected the data in the form of written expressions (sentences) by observing students’ analyzing skill processes when they examined their peers’ narrative compositions through comment feature in their peers’ captions. The findings showed that the activities of examining peers’ narrative compositions posted in instagram was belong to the real and meaningful transfer learning of near transfer. Next, two students (middle and high achievers) could fulfill five out of eleven criteria of critical thinking skill. Furthermore, both students solved problems in their own compositions better than in their peers’ compositions. Unfortunately, the low achiever did not give any feedback comments to her peers’ compositions. Thus, she had not applied her analyzing skill yet. In short, the actual evidence of analyzing skill implementation when students analyze their peers’ narrative compositions posted in instagram is possible to justify. Keywords: examine, HOT skills, social media.